Extraction of bioactives from brown seaweed using sub and supercritical fluids: Influence of the extract on the storage stability of fish oil enrich mayonnaise - Hermund, Ditte B.; Liu, Wei; Holdt, Susan Løvstad; Jacobsen, Charlotte; Getachew, Adane Tilahun (Frontiers in Food Science and Technology, 2023)
This study aimed at extracting lipophilic and hydrophilic compounds from Nordic brown seaweed Fucus vesiculosus and to evaluate the extract’s ability to maintain the physical and oxidative stability of fish oil-enriched mayonnaise (80% fat, 1:4 fish oil: rapeseed oil) during storage (dark, up to 28 days). Three different types of extracts were obtained, one using supercritical carbon dioxide (lipophilic extract) and two using subcritical water extraction (hydrophilic extracts)—one on dry seaweed (Subcritical water extract (SCWE) and one on the residue from supercritical carbon dioxide extraction after extracting the lipophilic compounds (Subcritical water extract (SCWER). The extracts were characterized with respect to their antioxidant composition and in vitro antioxidant properties. Moreover, the extracts were added in concentrations of 2 g/kg mayonnaise, both individually or in combination to study synergistic effects between antioxidants with different polarity and locations in the mayonnaise system. Results showed that both types of extractsdelayed the oxidation of lipids; The hydrophilic extracts (SCWE and SCWER) were able toretard the formation of hydroperoxides, and subsequent formation of secondary oxidation products. However, no synergetic effect was found for the hydrophilic and hydrophobic extracts when they were applied in different phases of the mayonnaise. The metal chelating ability is suggested to be responsible for the observed better performance of the hydrophilic extracts. However, further studies are required to understand which specific components in the extract have contributed to metal chelating ability. In conclusion, the findings of the present study suggest hydrophilic and hydrophobic compounds from the Nordic seaweed F. vesiculosus can retard lipid oxidation in mayonnaise.